1999
DOI: 10.4269/ajtmh.1999.60.875
|View full text |Cite
|
Sign up to set email alerts
|

Reduced soluble transferrin receptor concentrations in acute malaria in Vanuatu.

Abstract: Abstract. Soluble transferrin receptor (sTfR) concentration is a sensitive index of iron deficiency when used in conjunction with ferritin measurements in adults. One advantage of this assay is that unlike ferritin it does not appear to be affected by a range of infectious and inflammatory conditions or by pregnancy, rendering it a promising adjunct to the diagnosis of iron deficiency in tropical populations. We have measured plasma sTfR concentrations in a group of malaria patients (n ϭ 21) and asymptomatic (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 24 publications
1
25
1
Order By: Relevance
“…However, as previously mentioned in contrast to our results others have observed positive 322 relationships between inflammation markers and sTfR (10)(11)(12)(13)(14) or shown that that sTfR 323 decreased in malaria (8). In addition to increased erythropoiesis, higher sTFR concentrations 324 in children with infections may also be due to poorer iron status.…”
contrasting
confidence: 71%
“…However, as previously mentioned in contrast to our results others have observed positive 322 relationships between inflammation markers and sTfR (10)(11)(12)(13)(14) or shown that that sTfR 323 decreased in malaria (8). In addition to increased erythropoiesis, higher sTFR concentrations 324 in children with infections may also be due to poorer iron status.…”
contrasting
confidence: 71%
“…However the low prevalence of SCI meant that inflammation had little impact on nutritional biomarkers in the present study ( Table 2). The results also suggest that sTfR concentrations were not affected by SCI although other workers have reported different results (40)(41)(42) . The prevalence of SCI will depend on the intensity of infections and the age of the individuals.…”
Section: Discussionmentioning
confidence: 53%
“…Higher TfR concentrations among people infected with malaria (Mockenhaupt et al, 1999;Stoltzfus et al, 2000;Menendez et al, 2001;Verhoef et al, 2001) have led investigators to suggest that the high TfR reflects increased erythropoeisis resulting from malaria induced hemolysis. Others, however, have reported lower TfR concentrations during malaria suggestive of blunted erythropoeisis (Williams et al, 1999;Beesley et al, 2000).…”
Section: Discussionmentioning
confidence: 93%